Water Environment Pollution and Its Countermeasuresin Hanjiang River Ecologic Economic Belt - ZHANG Zhongwang; CHEN Yao; XU Cungang (Renmin Zhujiang)
Based on the statistical analysis of water quality monitoring data of the Hanjiang River in the past 10 years, this paper introduces the current situation and main problems of water environment pollution in the Hanjiang River Ecologic Economic Belt. The results show that: (1) In general, the water quality of the mainstream of the Hanjiang River is good, but it develops in the wrong direction. (2) The water quality of tributary tends to be better, but the pollution in some tributaries is still serious. (3) The water quality of the main stream and tributary in the Danjiangkou reservoir area is stable, but the water pollution during the dry season is more serious. (4) The water blooms in the lower reaches of the Hanjiang River occurs more and more frequent. After analyzing the causes of the problems, the measures for protecting the water environment of the Hanjiang River Ecologic Economic Belt and promoting the sustainable utilization of water resources are proposed.